Bernard–Soulier Syndrome: An Update - Andrews, Robert K.; Berndt, Michael C. (Seminars in Thrombosis and Hemostasis, 2013)
Bernard–Soulier syndrome (BSS) is a rare inherited platelet bleeding disorder characterized by low platelet count and abnormally large platelets (macrothrombocytopenia). Platelets from BSS patients are typically defective in surface expression of glycoprotein (GP)Ib-IX-V, a platelet-specific adhesion-signaling complex, composed of GPIbα disulfide linked to GPIbβ, and noncovalently associated with GPIX and GPV. The major ligand-binding subunit, GPIbα, binds the adhesive ligands von Willebrand factor (VWF) or thrombospondin, counterreceptors on activated endothelial cells (P-selectin) or activated leukocytes (integrin αMβ2), and coagulation factors (thrombin, factors XI and XII, high-molecular-weight kininogen). The cytoplasmic domain of GPIb-IX-V interacts with the cytoskeletal protein, filamin-A via a binding site within the GPIbα cytoplasmic tail, and with structural-signaling proteins including calmodulin, 14–3-3ζ and the p85 subunit of phosphoinositide 3-kinase. GPIbα is physically/functionally co-associated on the platelet surface with the major platelet collagen receptor, GPVI. As such, it is easy to see how genetic defects impacting GPIb-IX-V expression or function can have significant consequences on normal platelet size, adhesion to VWF/collagen and/or stable thrombus formation, and why BSS is often associated with clinical bleeding. Furthermore, the rarity, multiple genetic causes, and variable clinical phenotype of BSS can complicate routine diagnosis. Here, we discuss how studies of BSS have contributed to platelet biology and recent studies to improve diagnosis and treatment.
Keywords: Bernard–Soulier syndrome; bleeding disorders; glycoprotein Ib-IX-V complex; platelets; von Willebrand factor